Determination in Galicia of the required beds at Intensive Care Units - Iván Area; Xurxo Hervada Vidal; Juan J. Nieto; María Jesús Purriños Hermida (Alexandria Engineering Journal, 2021)
By using a recent mathematical compartmental model that includes the super-spreader class and developed by Ndaïrou, Area, Nieto, and Torres, a procedure to estimate in advance the number of required beds at intensive care units is presented. Numerical simulations are performed to show the accuracy of the predictions as compared with the real data in Galicia.